Using Discovery Learning and Problem-Based Learning to Increase Students' Motivation for Accomplishment - Suhada, Sitti; Sunardi, Sunardi; Amali, Lanto Ningrayati; Katili, Muhammad Rifai; Lahinta, Agus; Kilo, Juriah R. (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
According to initial observations made during the Basics of Computer Network Engineering and Telecommunications course in class X at TKJ SMK Negeri 5 Gorontalo, students were generally still passive and did not participate much in their education, preferring to listen to what their teachers said. This research aims to analyse: (1) the influence of the Problem Based Learning model on students' achievement motivation; (2) the influence of the Discovery learning model on students' achievement motivation; and (3) differences in achievement motivation between classes treated with Problem Based Learning. This study used a Non-equivalent Control Group Design research design in conjunction with a Quantitative Quasi-Experimental research method. This design consists of two groups that are not randomly selected, then given a pre-test to find out whether there are differences between the experimental group and the control group. The analytical test tool used in testing this research is the Paired Sample T-test with the following test results: (1) The Problem Based Learning model influences students' achievement motivation as indicated by the Sig value; (2) the Discovery Learning model influences students' achievement motivation as indicated by the Sig value (2-tailed) of 0.000 < 0.05. These results show that there are differences in the average achievement motivation of students in classes given the Discovery Learning model; and (3) Apart from that, the independent t test showed that there was no difference in achievement motivation between classes given the Problem Based Learning model and classes given the Discovery Learning model.